CORE MEMBER AND THE SUCCESS OF REGIONAL ORGANIZATIONS: A STUDY OF INDIA’S ROLE IN SOUTH ASIAN ASSOCIATION FOR REGIONAL COOPERATION - Muhammad Farooq Shah; Hameed Ullah Khan (Policy Research Journal, 2025)
The South Asian Association for Regional Cooperation (SAARC) has failed to realize its potential in terms of regional trade and connectivity. In this regard, India, the core state of the organization, occupies an important role that is crucial to the future success and failure of SAARC in the realization of its stated objectives. The study attempts to analyze Indian relations with its neighbors before or after the creation of SAARC in 1985 and to see whether any change in its attitude is noticed or not towards its neighbors in the said periods. The research is qualitative and based on secondary data collected from books, journals, and newspapers. Thematic analysis is applied to analyze the data. To conclude, India has shown little flexibility in its behavior towards its neighbors, even after the establishment of SAARC in 1985. India should demonstrate generosity to settle issues with its neighbors if it wants to diminish small states' apprehensions towards the big brother. Accommodation of small state interests by India can lead SAARC to realize its potential in trade and commerce, like ASEAN and the European Union.